Analisis Unsur Intrinsik Cerpen “Layang-Layang” Karya Marya Bernadeth Tukan Menggunakan Pendekatan Objektif - Selvia Ardianti; Mega Nurhayati (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2023)
This research focuses on the analysis of intrinsic elements in the short story "Layang-Layang" by Marya Bernadeth Tukan using an objective approach. The research method used is qualitative descriptive, with the short story "Layang-Layang" by Marya Bernadeth Tukan as the resource. The data collection technique that the researcher used was to read carefully the entire contents of the short story. The analysis technique that researchers use is by examining and discussing the contents of the short story. The results of the analysis that the researchers got was the theme of an unexpected meeting, the characters are Waban and Abel. Waban's character is a loner, a seeker of peace, simple and spontaneous, with a high sense of curiosity, as well as leadership. Meanwhile, Abel's character is mysterious, has a high taste for art, is independent, firm and humble. Marya Bernadeth Tukan writes her story using a third person point of view, this is indicated by the use of the names "Waban, Ia, and Dia". The language style used in the short story is simple and descriptive. The author uses clear words in describing the environment, characters and events in the short story. The setting used is a grass field and a house with wooden walls in the morning and a peaceful atmosphere. The message contained in the short story is the importance of living life with comfort and happiness as the main focus.